Arah Baru Perencanaan Pendidikan Dan Implikasinya Terhadap Kebijakan Pendidikan - Abdul Muis Daeng Pawero (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2021)
Whether bad or qualified or poorly educated will be much influenced by the governance system. Educational governance systems will develop well when implemented through good systems by clean and professional managers. The system has been designed in detail by the government established through the number 19 of 2007 permendiknas on "Education Management Standards by the elementary and secondary education units". The minister is prepared by the government to set up a good, balanced, and sustainable governance system At the Inquiry planning level, program planning organized by educational institutions should reflect the vision, mission, objectives, and work plan, as a raw material or reference of education policy at the managerial level. This paper will discuss the educational planning process and work plan of educational institutions in order to achieve shared ideals for a better educational future.